The Burden of Family Caregivers in the Care of Type 2 Diabetes Mellitus Patients: A Literature Review - Setyoadi; Meiliana, Sindy Wahyuarista; Hakim, Faradinanta Oktavia; Hayati, Yati Sri; Kristianingrum, Niko Dima; Kartika, Annisa Wuri; Sandi, Prinovi Sapta (Al-Hijrah Indonesia, 2024)
Background: This literature review study is based on the increasing number of people with Type 2 Diabetes mellitus (DMT2) which has an impact on the burden of family caregivers. Chronic T2DM disease requires long-term treatment and has an impact on the physical, psychological, social, and economic family. The burden of family caregivers causes stress, burnout, helplessness, and depression. Purpose: This literature review is intended to analyze the burden of family caregivers experienced when helping to care for family members with T2DM. Methods: This study method uses a literature review design conducted on 10 articles obtained from 3 data bases, namely EBSCO, PubMed, and Science Direct. The keywords used in article searches are